Kepatuhan bank syariah di Indonesia dalam menjalankan kegiatan usahanya terhadap ketentuan syariah compliance - Mohammad Ghufron Az (Jurnal Cakrawala Hukum, 2020)
The focus of this research is on the compliance of Islamic banks in Indonesia in carrying out their business activities to the provisions of sharia compliance. The main objective of this research is to analyze the compliance of Islamic banks in Indonesia in carrying out their business activities against the provisions of sharia compliance as stipulated in the law on Islamic banking. The normative juridical approach and the empirical juridical approach were used in this study. The result of the research shows that in formal juridical terms it has been regulated in the law concerning Islamic Banking that in its operations, Islamic banks must continue to carry out Islamic principles as a whole (kaffah) and consistently (Istiqamah). The principle of prudence Sharia banks must deviate from the sharia principles that should be adhered to. As in the Mudharabah and Musyarakah Agreements, according to sharia principles, Islamic banks are not allowed to require collateral, because with the guarantee conditions the Mudharabah and Musyarakah agreements become null and void by law. If there is no guarantee, then the protection for the bank is very weak because there will be a lot of bad financing that will eventually harm the people who deposit funds in Islamic banks. Guarantee in the Mudharabah and Musyarakah agreements to prevent non-performing financing and in order to protect the people who deposit funds.How to cite item: Ghufron Az, M. (2020). Kepatuhan bank syariah di Indonesia dalam menjalankan kegiatan usahanya terhadap ketentuan syariah compliance. Jurnal Cakrawala Hukum, 11(2), 187-193. doi:https://doi.org/10.26905/idjch.v11i2.4396